Implikasi Strategis Peran Chief Happiness Officer (CHO) dalam Meningkatkan Kesejahteraan, Produktivitas dan Loyalitas Karyawan - Musri’ah Musri’ah; Noor Qaria Rahmawaty; Mochammad Isa Anshori (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
The role of the Chief Happiness Officer (CHO) is increasingly important in human resource (HR) management strategies in the modern era. This article discusses how CHO can appropriately contribute to improving employee well-being, productivity, and loyalty based on a review of the existing literature. CHO is tasked with creating a positive work environment by designing comprehensive well-being programs, such as flexibility at work, psychological support, and the development of an organizational culture that focuses on employee happiness. The research method used is a type of putaka with research data sources from books, journals, reports, news and other things related to the title. The results of the study show that the existence of CHO can significantly reduce work stress, increase employee engagement, and reduce turnover rates. However, there are still challenges in implementing the role of CHO, especially in the non-technology sector and small and medium enterprises (SMEs). This is evidenced by companies that implement CHO roles tend to experience a decrease in turnover rates, which shows that investing in employee well-being is not only beneficial to individuals, but also to the organization as a whole. For example, Coca-Cola, TikTok, EY, Deloitte, SAP. Therefore, the results of this article recommend the need for further research to measure the effectiveness of CHO in various industrial sectors as well as develop more precise measurement standards.